A Facile One-pot Synthesis and Heterocyclisation of (R)-2-amino-3-((aroylcarbamothioyl)thio)propanoic Acids. (March 2014) - Mohebat, Razieh; Kafrizi, Elahe
A series of ( R )-2-amino-3-((aroylcarbamothioyl)thio)propanoic acid derivatives have been synthesised by a one-pot, three-component reaction of L-cysteine with ammonium thiocyanate in the presence of various acid chlorides under solvent-free conditions in excellent yields. These compounds were converted to ( R )-2-thioxothiazolidine-4-carboxylic acid in water under reflux conditions.